The PEMBELAJARAN BERDIFERENSIASI MELALUI MODEL PROJECT-BASED LEARNING (PJBL) PADA MATA PELAJARAN EKONOMI; : ANALISIS STUDI IMPELEMENTATIF - Hasanah, Nofiatul; Hidayanti, Denok Mugi; Neviyani, Neviyani (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
This study aims to describe the implementation of the Project-Based Learning (PjBL) model in differentiated learning in the Economics subject at SMK Raudlatul Ulum Ledokombo Jember, as well as to identify the obstacles encountered during its implementation. The approach used is qualitative with a case study type. Data collection techniques include interviews, observations, and documentation. The research results show that PjBL is capable of enhancing student learning activity and understanding of economic material through the stages of project planning, collaborative-based implementation, and authentic evaluation. However, several obstacles were found, such as the limited understanding of PjBL by teachers, time constraints, and high administrative burdens. This research suggests the need for continuous training, the provision of adequate resources, and cross-functional collaboration to support the implementation of PjBL. The implications of this research reinforce the position of PjBL as an innovative strategy in contextual and learner-centered economic education.